Assessment of teachers' knowledge, training, perceptions and participation in environmental education at a Greek island - Ντάιου, Κωνσταντίνα-Μαρία (2016)
In our days, it is a fact that Environmental Education (EE) projects in Greek schools face many organizational and institutional problems, although they have been introduced into the Greek educational system, almost three decades ago. This survey elaborates on the practices of EE that educators use in Greece, through a case study, which was performed at Skyros Island. A thorough literature review took place and the concept of civic ecology was compared to the outmost goal of EE. The participants of this research were teachers from the Skyros island schools. The methodological tool was an interview, based on questions that extrapolated information on teachers’ knowledge on environmental issues and their training and related perceptions as environmental educators. Furthermore, the teachers’ personal perception on the validity of the on going environmental education school projects was assessed. Substantially, this research focused on educators’ opinions on EE and their willingness to participate in environmental projects.